Pregnancy and Childbirth Outcomes of Gestational Diabetes Mellitus: A Retrospective Cohort Study - Fatemeh Darsareh; Malihe Shirzadfard Jahromi; Amene Ranjbar; Mitra Shekari; Vahid Mehrnoush; Nasibeh Roozbeh (Disease and Diagnosis)
Background: Understanding the various outcomes of gestational diabetes mellitus (GDM) is essential for initiating a cascade of preparatory steps to address them. Therefore, this study aimed to evaluate the pregnancy and childbirth outcomes of GDM. More precisely, the study retrospectively assessed singleton pregnant mothers diagnosed with GDM who gave birth at a tertiary hospital in Bandar Abbas, Iran, between January 1st, 2020, and January 1st, 2022. Materials and Methods: To this end, pregnancy and childbirth outcomes were investigated, including the incidence of the need for induction of labor, placenta abruption, preterm birth, intrauterine growth restriction (IUGR), intrauterine fetal death (IUFD), meconium fluid, fetal distress, methods of delivery, perineal lacerations, and postpartum hemorrhage. The other outcomes were childbirth injury, shoulder dystocia, macrosomia, low birth weight, congenital malformation, neonatal asphyxia, need for cardiac and respiratory resuscitation, transfer to a neonatal intensive care unit (NICU), and newborn death. Results: The records of 7748 eligible mothers were included in the analysis. GDM was diagnosed in 1,087 (14%) mothers. Age was the only sociodemographic factor that significantly differed between GDM and non-GDM mothers. GDM mothers had a significantly higher risk of macrosomia (adjusted odds ratio [aOR]: 2.94, 95% confidence interval [CI]: 1.71–4.61, P<0.001), labor induction (aOR: 3.14, 95% CI: 1.72–6.95, P<0.001), instrumental delivery (aOR: 3.16, 95% CI: 1.51–3.87, P<0.001), IUFD (aOR: 1.95, 95% CI: 1.17–3.06, P<0.01), and NICU admission (aOR: 2.19, 95% CI: 0.99–3.82, P<0.01). Other common complications, such as cesarean section (CS), postpartum hemorrhage, shoulder dystocia, childbirth trauma, and extensive perineal lacerations, were not significantly different between GDM and non-GDM mothers. Conclusion: Despite the higher incidence of labor induction and instrumental delivery, no significant association was found between GDM and adverse maternal outcomes. Regarding neonatal outcomes, GDM was linked to macrosomia, IUFD, and NICU admission.